Geochemistry of arsenic and heavy metals in pyrite ash - Theorin, Gunilla (2015)
This thesis was part of a project at the Swedish Geotechnical Institute aiming at investigating the geochemistry of heavy metals and arsenic in pyrite ash. The spe-cific aims with this work were to extend the knowledge on solubility control mechanisms of metals in pyrite ash and how the sorption ability of the ash was dependent on content of iron (hydr)oxides. Pyrite ash is a waste product from the roasting process of pyrite ore when producing sulphur dioxide. Sampling was per-formed at the former pulp mill Bergvik sulfit and leaching and selective extraction tests were performed on the material. EDTA-extractable concentrations of Cd, Cu, Pb, Zn and oxalate extractable con-centrations of Al, Fe and As were used as input in the geochemical equilibrium model Visual MINTEQ together with macro-cations, anions and DOC obtained from the pH leaching test. The predicted solution concentrations of Al, Fe, Cd, Cu, Pb, Zn and As from the model were compared to the pH leaching measurements. The model predicted the concentrations of Al, Cd, Zn and Cu very well without any parameterisation. The estimates for Pb and Fe were not as well matched with the experimental data which emphasises the need for further research on filter size and colloidal particles in solution. Too few measurements above detection limit were obtained for As to get a good verification of the model. The mechanism controlling the solution concentration at natural pH (6.5 – 7.1) for Al and Cu seemed to be precipitation of a mineral phase and for Cd, Pb, Zn and As complexation to (hydr)oxide surfaces. At alkaline pH the solution concentration of Zn was controlled by precipitation. Overall this approach, with leaching and selective extraction tests together with geochemical modelling, seems to be promising in the risk assessment of contami-nated soils.